Association Between Unequal Division of Caregiving Work and South Korean Married Women's Depressive Symptoms - Park, Minah; Jang, Jieun; Joo, Hye Jin; Kim, Gyu Ri; Park, Eun-Cheol (Frontiers in Public Health, 2022)
Background: A disproportionate amount of family caregiving can negatively impact married women's mental health. This study aims to examine the relationship between depressive symptoms in South Korean women and the satisfaction with their husband's participation in family caregiving. Methods Raw data from 1,515 of the participants in the 2014, 2016, and 2018 Korean Longitudinal Survey of Women and Families were analyzed. Satisfaction with husbands' participation in family caregiving was classified as satisfied, less satisfied, and not satisfied. The survey used the Center for Epidemiologic Studies Depression Scale to measure depressive symptoms. The association was examined using a generalized estimating equations model. Results Results indicated 22.2% of the participating women reported depressive symptoms. Women who reported dissatisfaction with their husband's participation in caregiving were 2.54 times more likely to report depressive symptoms than the women who were satisfied. Subgroup analysis indicated that women with higher levels of education, were more likely to have depressive symptoms when they were not satisfied with their husbands' participation in caregiving. Conclusion Married women who reported being dissatisfied with their husbands' participation in caregiving were more likely to report depressive symptoms. These results suggest the need to create environments with fair distribution of caregiving duties to minimize depressive symptoms in women.